Peningkatan Kualitas Media Pemasaran Tazkiya Souvenir dengan Web Profil - Rimawati, Elistya; Wawan Laksito Yuly Saptomo; Ari Wibowo (Jurnal Pengabdian Masyarakat Teknologi dan Pendidikan (MANTAP), 2024)
UMKM Tazkiya Souvenir produces various kinds of souvenirs for training activities or celebrations. To expand the marketing reach, UMKM Tazkiya Souvenir needs to utilize internet media. The purpose of this service activity is to assist Tazkiya Souvenir in increasing a wider marketing reach by utilizing Web Information. Data collection methods include observation, interviews, and literature studies. Web information contains superior products, profile videos, how to order, UMKM addresses, telephone numbers, and admin log in pages. The making of this web profile is expected to help marketing Tazkiya Souvenir UMKM products in the current digital era. The use of Web Profiles makes Tazkiya Souvenir UMKM products more easily recognized by the wider community without distance and time restrictions, so as to increase sales.